REVITALIZING POST-MINING LAND: THE ROLE OF THE LAND BANK IN PROMOTING SOCIAL JUSTICE AND ENVIRONMENTAL SUSTAINABILITY - Wardhani, Dwi Kusumo (Masalah-Masalah Hukum, 2025)
This research examines the role of the Land Bank in Indonesia’s legal policy, focusing on state rights and the pursuit of social justice. According to Article 33 of the 1945 Constitution, the state holds the authority to control land and natural resources, ensuring their use for public welfare. The Land Bank is a key institution in managing land, particularly post-mining areas, to address the environmental damage and ensure equitable benefits for local communities. However, in practice, the implementation of the Land Bank has faced several obstacles, including insufficient socialization, weak state control over land, and land disputes stemming from an underdeveloped land registration system. Using an empirical juridical method, this study analyzes secondary data from legal texts, doctrines, and previous research, while primary data is gathered through interviews with stakeholders from PT Timah Tbk, the Ministry of Agrarian Affairs, and the Environmental Agency of East Belitung. The findings highlight the need for legal harmonization between key laws, such as the Basic Agrarian Law, the Mineral and Coal Law, and the Environmental Law, to create a clear framework for the Land Bank’s operation. The research proposes a comprehensive Land Bank model that integrates a strong institutional structure, skilled human resources, and effective administrative systems. Additionally, it stresses the importance of incorporating environmental sustainability and social justice principles in the management of post-mining land to promote the welfare of affected communities and prevent land speculation.